Investigation of networks underlying hyperkinetic seizures utilizing ictal SPECT. (11th August 2020) - Kheder, Ammar; Thome, Ursula; Aung, Thandar; Krishnan, Balu; Alexopoulos, Andreas; Wu, Guiyun; Wang, Irene; Kotagal, Prakash
Abstract : Objective: To study neural networks involved in hyperkinetic seizures (HKS) using ictal SPECT. Methods: We retrospectively identified 18 patients with HKS evaluated at the Cleveland Clinic between 2005 and 2015 with video-EEG monitoring and ictal SPECT. Semiology was confirmed by the consensus of 2 epileptologists' independent reviews and classified as type 1, 2, or 3 HKS. SPECT data were analyzed by 2 independent physicians using a z score of 1.5. Ictal hyperperfusion patterns for each group were analyzed visually and with SPM. Spatial normalization to Montreal Neurological Institute space for each patient's data was performed, followed by flipping of data from patients with left-sided ictal onset to the right side. Finally, an average z score map for each group was calculated. Results: Visual analysis and SPM identified different patterns of ictal hyperperfusion in the 3 subtypes of HKS. Type 1 seizures showed hyperperfusion in a more anteriorly located network involving the anterior insula, orbitofrontal cortex, cingulate, and anterior perisylvian region and rostral midbrain. Type 2 seizures were associated with hyperperfusion in a more caudally located network involving the orbitofrontal cortex, cingulate (middle and posterior), basal ganglia, thalami, and cerebellum. Type 3 seizures showed a mixed pattern of SPECT hyperperfusion involving the temporal pole and anterior perisylvian region. Conclusions: Each of the 3 different semiologic subtypes of HKS is associated with distinct patterns of hyperperfusion, providing further insight into the neural networks involved. This knowledge may inform placement of invasive EEG electrodes in patients with HKS semiology undergoing presurgical evaluation.